A Guideline of Earned Value Method (EVM) Implementation as Decision Baseline on Acceleration Solutions for Construction Project Scheduling - Zetta Rasullia Kamandang,; I Nyoman Dita Pahang Putra,; Anna Rumintang Nauli, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Implementing an efficient performance monitoring system is necessary to complete a facility building project on time, on budget, and by established standards and specifications. Inappropriate system monitoring process could lead to project failures such as delay which commonly occurs. If the delay happens, it is necessary to accelerate work productivity to overcome it. Earned value method (EVM) is one of the suggested global standards for measuring project performance. It effectively combines scope, cost, and schedule metrics and can provide a clear picture of the state of the project as of the control date. It also predicts the time prolong and completion budget. This paper proposes a guideline to implement EVM as a decision baseline on acceleration solutions for construction project scheduling by conducting an article review, since the EVM can predict the project’s time estimates at completion (TE). According to the guideline, when arranging network planning based on construction actual work performed, it is essential to use TE as the completion time. From the critical activities in network planning, contractors can conduct the acceleration process such as additional work hours (overtime) and additional manpower. This acceleration scenario later could be implemented in the project as the solution to overcome the delay.